2017
DOI: 10.1523/eneuro.0052-17.2017
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Changes in Component Processes of Working Memory

Abstract: Working memory (WM) entails maintenance and manipulation of information in the absence of sensory input. This study investigated the trajectories and neural basis of these component processes of WM functions in aging. Longitudinal human functional magnetic resonance imaging (fMRI) data are presented from 136 older individuals (55–80 years) who were scanned at baseline and again 4 years later. We obtained evidence that age-related changes in parietal and frontal components of the WM core network are dissociable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
19
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 42 publications
5
19
0
Order By: Relevance
“…Whereas maintenance required only maintaining information in WM, the manipulation condition also required the active transformation of task information in WM. Robust fMRI responses to the task in canonical WM areas, FPN and DAN, have been reported in prior studies 74,75 . Prior to scanning, participants practiced four 1-minute blocks in each condition to ensure they fully understood the tasks.…”
Section: Verbal Working Memory Tasksupporting
confidence: 60%
“…Whereas maintenance required only maintaining information in WM, the manipulation condition also required the active transformation of task information in WM. Robust fMRI responses to the task in canonical WM areas, FPN and DAN, have been reported in prior studies 74,75 . Prior to scanning, participants practiced four 1-minute blocks in each condition to ensure they fully understood the tasks.…”
Section: Verbal Working Memory Tasksupporting
confidence: 60%
“…However, a more recent study demonstrated that smaller hippocampus size is significantly associated with lower performance in episodic memory, working memory, processing speed, and executive function tasks 102 . Similarly to motor function, it has been shown that older adults recruit additional brain regions during memory tasks [103][104][105] .…”
Section: Modification Of Brain Functions During Agingmentioning
confidence: 99%
“…The aging human brain is characterized by grey (Crivello, Tzourio-Mazoyer, Tzourio, & Mazoyer, 2014;Jäncke, Mérillat, Liem, & Hänggi, 2015) and white (Bender, Völkle, & Raz, 2016;Hirsiger et al, 2016) matter changes in cortical (Crivello et al, 2014) and subcortical (Ziegler et al, 2012) brain regions. Such anatomical alterations are accompanied by an inter-individual variable decline of several cognitive functions (Shafto & Tyler, 2014), including attention (Erel & Levy, 2016;Fama & Sullivan, 2015), short-term memory, working memory (Rhodes & Katz, 2017;Rieckmann, Pudas, & Nyberg, 2017) as well as episodic memory (Fjell et al, 2016). However, due to compensatory functional mechanisms that are reflected by the recruitment of auxiliary brain regions or increased functional connectivity, there is no simple relationship between aging, brain changes and the preservation of cognitive functions (Shafto & Tyler, 2014).…”
Section: Introductionmentioning
confidence: 99%